2020
DOI: 10.1021/acsami.0c06476
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of Ga2O3/ZnO Composite Films for High-Performance Forming-Free Resistive Switching Memory

Abstract: The resistive switching behavior in resistive random access memories (RRAMs) using atomic-layer-deposited Ga 2 O 3 / ZnO composite film as the dielectric was investigated. By alternatively atomic-layer-depositing Ga 2 O 3 and ZnO with different thickness, we can accurately control the oxygen vacancy concentration. When regulating ZnO to ∼31%, the RRAMs exhibit a forming-free property as well as outstanding performance, including the ratio of a high resistance state to the low resistance state of 1000, retentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 49 publications
1
32
0
Order By: Relevance
“…The V O defects are observed to be suppressed [212], and the film resistivity decreases at 800 o C. The method support deposition at a fraction of time usually used by the ALD method, high quality of deposition with high throughput, and support area-selective deposition [210]. Li et al [177] recently demonstrated how to precisely control the content of Zn and V O concentration in an ALD deposited Ga 2 O 3 /ZnO composite resistive layer via adjusting the number of the composite resistive layer cycles during the ALD power, the device shows very-low resistivity and unable to produce switching behavior (b) Device developed using 50 W RF power, the device shows an LRS that leads to its failure even with the application of the negative voltage it refused to switch to the HRS (c) Device made with RF power of 100 W (d) Device developed using RF power of 200 W. The 100 W and 200 W RF power produce devices with counter-clockwise bipolar switching characteristics [201].…”
Section: Effect Of Deposition Parametersmentioning
confidence: 89%
See 3 more Smart Citations
“…The V O defects are observed to be suppressed [212], and the film resistivity decreases at 800 o C. The method support deposition at a fraction of time usually used by the ALD method, high quality of deposition with high throughput, and support area-selective deposition [210]. Li et al [177] recently demonstrated how to precisely control the content of Zn and V O concentration in an ALD deposited Ga 2 O 3 /ZnO composite resistive layer via adjusting the number of the composite resistive layer cycles during the ALD power, the device shows very-low resistivity and unable to produce switching behavior (b) Device developed using 50 W RF power, the device shows an LRS that leads to its failure even with the application of the negative voltage it refused to switch to the HRS (c) Device made with RF power of 100 W (d) Device developed using RF power of 200 W. The 100 W and 200 W RF power produce devices with counter-clockwise bipolar switching characteristics [201].…”
Section: Effect Of Deposition Parametersmentioning
confidence: 89%
“…Thus, this opens up a new trend towards achieving significant data densities in RRAM devices. [177]. The current conduction mechanism (CCM), as shown in Fig.…”
Section: Multi-layered Zno Based Rrammentioning
confidence: 99%
See 2 more Smart Citations
“…require high-density storage devices to store and read the data requested in the application. , Silicon-based “flash” memory is undoubtedly the most successful nonvolatile memory at present, but people’s demand for storage density continues to increase, and the miniaturization of devices is becoming increasingly difficult. The size of the device is approaching the physical limit, so it is necessary to develop a new type of nonvolatile memory with high performance and low power consumption. Resistive random access memory (RRAM) has attracted widespread attention in recent years because of its fast read and write speed, simple structure, and low power consumption. It can store data by not only the high resistance state (HRS) and the low resistance state (LRS) but also the intermediate states between HRS and LRS; furthermore, RRAM can also be used for other functions, such as multilevel data storage and simulation of biological synapses. A variety of materials have been reported to exhibit memory behavior, such as metal oxides, organic polymers, perovskite materials, and so on. With the development of technology, researchers are devoting more attention to some aspects of the device performance, such as pollution-free, low power consumption, recyclable regeneration, and high-density storage .…”
mentioning
confidence: 99%